Optimization of the Convolutional Neural Network Method Using Fine-Tuning for Image Classification of Eye Disease - Wulandari, Vivi; Putra, Anggyi Trisnawan (Recursive Journal of Informatics, 2024)
The eye is the most important organ of the human body which functions as the sense of sight. Most people wish they had healthy eyes so they could see clearly about life around them. However, some people experience eye health problems. There are many types of eye diseases ranging from mild to severe. With advances in technology, artificial intelligence can be used to classify eye diseases accurately, one of which is deep learning. Therefore, this study uses the Convolutional Neural Network (CNN) algorithm to classify eye diseases using the VGG16 architecture as a base model and will be combined using a fine-tuning model as an optimization to improve accuracy.